Poster presentation Investigating acute and chronic mixture effects of pharmaceuticals towards Daphnia magna - Vasquez Christodoulou, Marlen (My University, 2026)
Vasquez MI, Tarapoulouzi M, Michael C, Fatta- Kassinos D, Investigating acute and chronic mixture effects of pharmaceuticals towards Daphnia magna, Poster presentation, 15th EuCheMS International Conference on Chemistry and the Environment, Leipzig, Germany, 20-24 September 2015.